The law of nations and natural law, 1625-1800 - Law of Nations and Natural Law, 1625-1850 (Conference) (2015 Université de Lausanne); Zurbuchen, Simone 1960- ([Erscheinungsort nicht ermittelbar] Brill, 2019)
Twelve international scholars offer innovative studies of the law of nations from the Peace of Westphalia to the Enlightenment. The focus is on little known contexts and sources, and on novel interpretations of classics in the field. Readership: Philosophers, historians, legal scholars and political theorists interested in the history of international law, and anyone concerned with modern natural law and Emer de Vattel’s Law of Nations
English
Keywords: Legal History; Legal history; Konferenzschrift; Aufsatzsammlung